Scoping Review on Use of Drugs Targeting Interleukin 1 Pathway in DIRA and DITRA - Francisco Gómez-García; Juan L. Sanz-Cabanillas; Isabel Viguera-Guerra; Beatriz Isla-Tejera; Antonio Vélez-García Nieto; Juan Ruano (Adis, Springer Healthcare, 2018)
Abstract Introduction Deficiencies in interleukin (IL)-1 receptor (IL-R) antagonist (DIRA) and IL-36R antagonist (DITRA) are rare genetic autoinflammatory diseases related to alterations in antagonists of the IL-1 pathway. IL-1 antagonists may represent therapeutic alternatives. Here, we aim to provide a scoping review of knowledge on use of IL-1-targeting drugs in DIRA and DITRA. Methods An a priori protocol was published, and the study was conducted using the methodology described in the Joanna Briggs Institute Reviewer's Manual and the recently published PRISMA Extension for Scoping Review statement. A three-step search using MEDLINE and EMBASE databases until March 2018 with additional hand searching was performed. Data charting was performed. The search, article selection, and data extraction were carried out by two researchers independently. Results Twenty-four studies on use of anti-IL-1 drugs were included [15 studies including patients with diagnosis of DIRA (n = 19) and 9 studies including patients with diagnosis of DITRA (n = 9)]. Most studies followed a multicenter observational design. Among all patients who received treatment with anti-IL-1 drugs, nine and four mutations in IL1RN and IL36RN were found, respectively. Patients with DIRA were treated with anakinra (n = 17), canakinumab (n = 2), or rinolacept (n = 6). All patients with DITRA were treated with anakinra, and only one case was also treated with canakinumab. Time-to-response frequencies were evaluated as immediate, short, and medium-long term for DIRA (17/17, 15/17, and 9/10, respectively) and DITRA (7/9, 3/9, and 2/9, respectively). Most DITRA patients in whom anti-IL-1 treatment failed experienced good response to anti-tumor necrosis factor alpha or anti-IL-12/23 drugs. The safety profiles of treatments were similar in both diseases. Conclusions Evidence on use of anti-IL-1 drugs in DIRA and DITRA is scarce and based on observational studies. Larger studies with better methodological quality are needed to increase confidence in use of these drugs in patients with DIRA and DITRA.